Morphological Process of Suffix -shii in Japanese - Wedayanti, Ni Putu Luhur (Lingual Journal of Language and Culture, 2016)
Japanese has many compound words which are used productively in daily life. Compounding words is done in various ways in accordance with the morphological processes required. Compounding basic words discussed in this article begins with the reduplication process of basic words and continues with the process of affixation by adding the suffix -shii on the reduplication results. The data is collected from articles on social media and related references. The discussion shows that some of the words experiencing the morphological process has changes in their word class and their meaning but most of them does not have any change either their word class or their meaning.
Keywords: morphological processes, suffixes -shii, Japanese language.